Use of simulation model to improve the manual operation procedures of an irrigation canal (Kirindi Oya - Sri Lanka) - Rey, J.; Malaterre, P.O.; Baume, J.P. (1993)
Following a presentation of the operational challenges faced by the canal managers, the use of a simulation model to improve the manual operation procedures of an irrigation canal is detailed. The pilot field site for this IIMI-CEMAGREF collaboration is the Kirindi Oya Right Bank Main Canal (Sri Lanka). The simulation model RBMC is a fully interfaced hydrodynamic model solving complete Saint-Venant equations. Its first applications provided detailed information on canal behavior and a diagnosis on the present manual operation procedures. Its integration in a broader Management Information System provided canal managers with a decision- support package helping them to improve operational procedures. These improvements contributed to increase the water use efficiency.